ESTIMASI KEDALAMAN TITIK CURIE, GRADIEN GEOTERMAL DAN ALIRAN PANAS MENGGUNAKAN METODE ANALISIS SPEKTRAL DATA AEROMAGNETIK DAERAH JAWA BARAT - Nuril Haq, Aufan
Most of Indonesia's territory has a series of volcanoes and has a very high potential for geothermal energy. Geothermal energy needs to be developed in Indonesia because geothermal is one of the environmentally friendly energy and is a renewable form of energy source. Areas that have the potential for geothermal energy can be further explored with magnetic methods through the depth of the Curie point. In this research, the estimation of Curie point depth will be determined using the spectral analysis method on total magnetic anomaly data from the Coordinating Committee for Geoscience Programmes in East and Southeast Asia in 2021 in the West Java area. Spectral analysis of the total magnetic anomaly map is used to obtain the top depth (Zt) and centroid depth (Z0). From these two depths, calculations are carried out to obtain the basal depth of the magnetic source or the depth of the Curie point (Zb). By obtaining the depth of the Curie point, it can also analyze the geothermal gradient and heat flow to see the geothermal system in the study area. The West Java area is divided into 93 blocks, with an area of each block of 40×40 km and there is an overlap between blocks of 50% to close the measurement space. The calculation results show the depth of the Curie point in the study area ranges from 11.4 to 24.5 km, the geothermal gradient ranges from 23.7 to 50.9 oC/km, and the heat flow ranges from 59.2 to 127.4 mW/m2. The presence of volcanoes and surface manifestations is represented by shallow Curie point depth values and high geothermal gradient and heat flow values.